Penguatan Moderasi Sosio-Religius Anak Usia Dini Berbasis Kearifan Lokal - Ali, Musyafa; Prawening, Cesilia; Marlina, Marlina (AS-SABIQUN, 2023)
Religion is often used as a basis by a person or group to commit harmful acts of extremism. This is certainly contrary to the provision that religion as a norm of life. Religion and society have an interrelation that can be observed from the symptoms of expression reflected in the behavior of religious believers. The purpose of this study is to describe, analyze, and integrate forms of local wisdom activities as an effort to strengthen early childhood socio-religious moderation. This type of research is a field research using a phenomenological approach, where researchers will observe and investigate directly the phenomena that occur in the field related to socio-religious moderation and local wisdom. This research was conducted in Painggangan Village, Banyumas Regency. The source of informants is parents. Data collection is carried out by observation and interviews, while documentation is used as support. Analysis is carried out by means of data reduction, data presentation and drawing conclusions and data verification. The result of this study is that there are several traditions that are still carried out by the Pasinggangan Village Community of Kaupaten Banyumas, where these traditions also have an impact on the socio-religious aspects of children, these traditions are, among-among, suran, earth alms, pilgrimage, ebeg art, and jamasan. From the tradition that is still carried out, it is known that there are cultural, social, and religious elements where in its implementation children are involved either directly or indirectly so that children feel the impact of these activities.